Charge-tunable absorption behavior of DNA on graphene1. Issue 24 (28th June 2015) - Kong, Zhe; Zheng, Wei; Wang, Qi; Wang, Hongbo; Xi, Fengna; Liang, Lijun; Shen, Jia-Wei
<x xml:space="preserve">Abstract</x> Charge-tunable absorption behavior of DNA on graphene: 0 is uncharged; − is negative charge; + is positive charge.